Pengaruh Subtitusi Limbah Marmer Terhadap Kuat Tekan dan Daya Serap Air pada Beton Porous - Nadir, Nadya Adillah; Mustakim, Mustakim; Kasmaida, Kasmaida (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Marble waste from the stone-cutting industry is often underutilized and has the potential to pollute the environment. One alternative use is as a substitute in porous concrete, which generally has low compressive strength and high water absorption. The addition of marble waste is expected to fill excess voids, thereby increasing compressive strength and reducing water absorption. This study aims to analyze the effect of marble waste substitution on compressive strength and water absorption in porous concrete using an experimental research method conducted in the Structures and Materials Laboratory of Muhammadiyah University of Parepare. The results showed that 5% marble waste substitution in porous concrete increased compressive strength at 14 and 28 days, from 16.085 MPa to 16.743 MPa and from 21.390 MPa to 21.728 MPa, respectively. Water absorption tended to decrease, from 0.835% to 0.437% at 14 days, although it increased slightly at 28 days, from 0.172% to 0.281%. This indicates that marble waste can be used as an environmentally friendly additive without compromising the quality of the concrete.